Household Risk Management in Senegal - De Vreyer, Philippe (World Bank, Washington, DC, 2013)
This study explores risk management and risk coping by Senegalese households, focusing particularly on individual vulnerability to shocks within the household by (1) documenting the risks faced by households in Senegal by looking at the frequency and types of shocks that households are exposed to, as well as the positive and negative ways in which households cope; (2) assessing the impact of the shocks on household per capita consumption and on human capital accumulation in an attempt to identify which of the household characteristics facilitate coping; and (3) addressing the way shocks affect the intra‐household allocation of resources. Results show that bigger households seem to benefit more from positive shocks, while single parent households or households headed by unmarried women are more affected by negative shocks than other households. Additionally, the authors reveal that poor households are more vulnerable than non‐poor to shocks, and that asset holding helps in smoothing the impact of shocks on consumption.